Estudo da influência do arranjo de proteção em transdutores piezoelétricos aplicados na técnica da impedância eletromecânica em estruturas de concreto - Gomes, Lucas (2024)
The proposed study aims to investigate various modifications to improve the mechanical properties of the piezoelectric transducer used in the ISHM technique for concrete structures. Specifically, the focus is on developing a new protective layer for the piezoelectric transducer, enhancing its strength and deformation properties while also ensuring efficient electromechanical coupling between the interface and the piezoelectric transducer. The effectiveness of the new protective layer is evaluated using the finite element method (FEM) in the COMSOL Multiphysics® software. This simulation allows for exploring different modifications, such as varying the mechanical composition of the coating, altering the thickness of the protective layer, and selecting different elements for composite formation. Subsequently, the protective layer was tested in experimental trials to validate the results obtained from the computational simulation. The transducer's performance was assessed by analyzing the wave propagation response, comparing the impedance signal obtained by the transducer in concrete elements both with and without damage. To ensure data reliability, various statistical metrics were employed to evaluate its precision and accuracy. The protective set consisted of adding an aluminum sheet along with the epoxy coating to improve the signature response. Following this approach, it was possible to verify that the proposed model, using an aluminum plate along with the epoxy resin, presented satisfactory damage detection responses and robustness in the FEM. Analyzing the experimental results, it is evident that this research validates the proposed model through the analyzed metrics, thus providing greater reliability in the obtained responses.